Impact Assessment Of Community Extension Services of Saint Joseph Institute of Technology at Village Lumbocan, Butuan City - Herrera, Fernando T.; Cacayan, Prospero R. (JPAIR Multidisciplinary Research, 2010)
This study aimed to examine the impact of the Community Extension Services (CES) of Saint Joseph Institute of Technology-Butuan City which have been rendered for three (3) years at Village Lumbocan. Its main objective is to assess the effectiveness of the programs demonstrated in terms of health services, safety and security, infrastructure and technical skills development, community livelihood and enrichment program, literacy training, environmental management and development, good governance, and coastal rehabilitation. Results are based on students and household survey and focus group discussion. The findings highlight the data gathered from among the recipients of the community extension programs at village Lumbocan as offered by the different colleges of Saint Joseph Institute of Technology-Butuan City. Results showed that the institution being represented by the seven (7) colleges and the Graduate School was socially responsive to the needs and sincere in its role of uplifting the quality of life of the residents of village Lumbocan. Salient findings of this research endeavor confirmed the importance of students to realize their experiential learning that transforms them to become humane individuals who, together with coordinators and volunteers, are committed to be part of the humane extension program at village Lumbocan.